The role of self-efficacy in managing type 2 diabetes and emotional well-being: a cross sectional study - Jamal Ataya; Jameel Soqia; Nour Albani; Nour Kara Tahhan; Massa Alfawal; Oubada Elmolla; Ahmad Albaldi; Raneem Alnassif Alsheikh; Younes Kabalan (BMC Public Health)
Abstract Background Managing chronic conditions like Type 2 diabetes presents significant challenges, with self-efficacy—one’s belief in their ability to manage their health—playing a crucial role. This study investigates the influence of self-efficacy on emotional distress and health outcomes among Type 2 diabetes patients. Methods We conducted a cross-sectional study in Damascus with 336 Type 2 diabetes patients from three healthcare facilities. Data were collected through face-to-face interviews using validated questionnaires: the Diabetes Management Self-Efficacy Scale (DMSES), Problem Areas in Diabetes (PAID-5), and the World Health Organization-Five Well-being Index (WHO-5). Results Analysis revealed that female gender and older age are significant factors influencing diabetes distress, with higher levels of distress observed in females and older patients. A negative correlation was found between self-efficacy and age, indicating reduced confidence in diabetes management among older individuals. Treatment modalities, such as oral hypoglycemic agents, were positively associated with higher self-efficacy. Significant associations were found between diabetes duration, age, and diabetes distress (PAID-5 scores), while self-efficacy (DMSES scores) varied based on treatment types. Conclusions Despite high levels of diabetes distress and low psychological well-being, patients demonstrated commendable self-efficacy in managing their diabetes. Targeted interventions should address the needs of elderly female patients and those undergoing specific treatments to improve care outcomes. This study highlights the importance of tailored support and a holistic approach to diabetes management.